2017
DOI: 10.1186/s12944-017-0461-2
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of various ratios of DHA/EPA supplementation on high-fat diet-induced liver damage in mice

Abstract: BackgroundA sedentary lifestyle and poor diet are risk factors for the progression of non-alcoholic fatty liver disease. However, the pathogenesis of hepatic lipid accumulation is not completely understood. Therefore, the present study explored the effects of dietary supplementation of various ratios of docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) on a high-fat diet-induced lipid metabolism disorder and the concurrent liver damage.MethodsUsing high-fat diet-fed C57BL/6 J mice as the animal model,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 44 publications
(64 reference statements)
2
45
0
Order By: Relevance
“…Many studies have found that purified compounds of plants or fish may improve NAFLD [24][25][26][27]. For example, 6-gingerol is linked to reduced body weight and inhibition of lipid accumulation of hepatocytes in obese mice [28].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have found that purified compounds of plants or fish may improve NAFLD [24][25][26][27]. For example, 6-gingerol is linked to reduced body weight and inhibition of lipid accumulation of hepatocytes in obese mice [28].…”
Section: Discussionmentioning
confidence: 99%
“…It also reduced the expression of lipid metabolism genes, such as Sterol regulatory element-binding protein-1-C (SREPB-1C), Stearoyl-CoA desaturase-1 (SCD-1), Acetyl-CoA carboxylase (ACC-1), and PPAR-γ, lowered the expression of proteins c-Jun and c-Fos levels, which are proteins related to inflammatory responses of metaflammation, activating protein-1 (Ap-1), and weakening the activation of Ap-1. Additionally, serum levels of pro-inflammatory cytokines (IL-6 and IL-1β) were reduced with the DHA/EPA ratio of 1:2 [ 132 ].…”
Section: Fatty Acids and Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%
“…EPA/DHA ratio and sum of EPA + DHA As EPA and DHA differ in their biological functions, 24 these fatty acids perform differently in the organism. Consequently, some biological mechanisms require an adequate EPA/DHA ratio, 3 and pharmaceutical applications require the ratio to be adequately controlled.…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 99%